2012
DOI: 10.1101/gr.130062.111
|View full text |Cite
|
Sign up to set email alerts
|

Chimeras taking shape: Potential functions of proteins encoded by chimeric RNA transcripts

Abstract: Chimeric RNAs comprise exons from two or more different genes and have the potential to encode novel proteins that alter cellular phenotypes. To date, numerous putative chimeric transcripts have been identified among the ESTs isolated from several organisms and using high throughput RNA sequencing. The few corresponding protein products that have been characterized mostly result from chromosomal translocations and are associated with cancer. Here, we systematically establish that some of the putative chimeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
154
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 74 publications
10
154
0
Order By: Relevance
“…Trans-splicing is a regular feature of the genome expression process in certain organisms [47], and it serves as a mechanism for protein diversification by creating novel exon combinations in many taxa [48]. Recent data indicate that trans-splicing occurs more frequently than previously believed [49].…”
Section: Formatting For Post-transcriptional Rna Processing and Editingmentioning
confidence: 99%
“…Trans-splicing is a regular feature of the genome expression process in certain organisms [47], and it serves as a mechanism for protein diversification by creating novel exon combinations in many taxa [48]. Recent data indicate that trans-splicing occurs more frequently than previously believed [49].…”
Section: Formatting For Post-transcriptional Rna Processing and Editingmentioning
confidence: 99%
“…Proteome complexity is highlighted by recent studies showing that phenotype is not entirely determined by information encoded in the translated genome; PTMs, noncoding RNAs (including microRNAs), epigenetic changes, and protein-protein interaction networks affect phenotype. 5,6 The ultimate goal of cardiovascular proteomics is to harness and better comprehend this molecular complexity as a means to discover new, effective strategies for the prevention, identification, and treatment of cardiovascular disease.…”
Section: The Foundation Of Proteomicsmentioning
confidence: 99%
“…Furthermore, it has been shown that transcription proceeds in the 59 direction beyond 65% of ENCODE gene boundaries, often integrating into the exonic structure of upstream genes; the role of such ''chimeric read-through RNAs'' remains largely unclear (Fig. 1B, model vii;Gingeras 2009;Djebali et al 2012b;Frenkel-Morgenstern et al 2012). Unfortunately, contemporary RNA-seq data sets remain a source of technical frustration; the reads generated are short in length, and it is no trivial task to assemble these fragments into full-length transcript models (Wang et al 2009;Martin and Wang 2011;Ozsolak and Milos 2011).…”
Section: New Technologies Can Aid Transcript Capture and Completionmentioning
confidence: 99%
“…In particular, a locus may generate multiple transcripts due to alternative splicing (AS) ) and read-through transcription (Fig. 1B;Frenkel-Morgenstern et al 2012), while the discovery of long noncoding RNAs (lncRNAs) suggests that most human transcripts may not encode proteins (Rinn and Chang 2012). In fact, the bulk of the genome appears to be ''pervasively'' transcribed (The ENCODE Project Consortium 2012), although the functional relevance of this process remains a source of debate (Ball 2013;Doolittle 2013;Graur et al 2013).…”
mentioning
confidence: 99%